The Use of Social Media in Teaching Listening Skills To Students in the Arabic Language Education Department: A Phenomenological Study at the Sultan Syarif Kasim State Islamic University in Riau - Wilsa Martiana; Yasmaruddin Bardansyah; Nandang Sarip Hidayat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore the experiences of Arabic Language Education students in utilizing social media for learning listening skills, supporting and inhibiting factors, as well as students' perceptions of the use of social media in learning Arabic listening skills. This study uses a qualitative approach with a phenomenological type. Data collection techniques included in-depth interviews and the distribution of Likert scale questionnaires to students. Interviews were conducted with several students majoring in Arabic language education. Meanwhile, the questionnaire aimed to identify and measure students' perceptions of the use of social media as a medium for learning listening skills. The results showed that students used social media, particularly YouTube, TikTok, and Instagram, as alternative learning spaces that were independent, flexible, and sustainable. The learning listening skills process was carried out through intensive repetition strategies, vocabulary recording, meaning search, and pronunciation imitation. The questionnaire data showed that YouTube was the most frequently used social media platform (45.5%) because it provided long-duration content and stable audio, followed by TikTok (40.9%) as a medium for listening practice, and Instagram (13.6%) as a supporting medium. Supporting factors for social media utilization include ease of access, flexibility of time and place, diversity of Arabic-language content, and exposure to authentic language. Meanwhile, inhibiting factors include digital distractions, notifications, advertisements, limited internet access, and excessive use. From a perceptual standpoint, students assessed that the use of social media had a positive impact on learning motivation, self-confidence, and listening skills. However, this impact was more dominant in receptive aspects than in productive skills. Thus, social media is considered effective as a supporting tool for learning listening skills.